High level trigger configuration and handling of trigger tables in the CMS filter farm - Bauer, G; Behrens, U; Boyer, V; Branson, J; Brett, A; Cano, E; Carboni, A; Ciganek, M; Cittolin, S; O'dell, V; Erhan, S; Gigi, D; et al. (Journal of physics. Conference series, 2008)
The CMS experiment at the CERN Large Hadron Collider is currently being commissioned and is scheduled to collect the first pp collision data in 2008. CMS features a two-level trigger system. The Level-1 trigger, based on custom hardware, is designed to reduce the collision rate of 40 MHz to approximately 100 kHz. Data for events accepted by the Level-1 trigger are read out and assembled by an Event Builder. The High Level Trigger (HLT) employs a set of sophisticated software algorithms, to analyze the complete event information, and further reduce the accepted event rate for permanent storage and analysis. This paper describes the design and implementation of the HLT Configuration Management system. First experiences with commissioning of the HLT system are also reported.